Muslim women in America : the challenge of Islamic identity today - Haddad, Yvonne Yazbeck, 1935- (Oxford University Press, 2006)
This text surveys the situation of women in Islam, focusing on how Muslim views about and experiences of gender are changing in the Western diaspora. It offers an overview of the teachings of the Qur'an and the Prophet Muhammad on gender, and analyses the ways in which the West has historically viewed Muslim women.